1984
DOI: 10.3109/03091908409018186
|View full text |Cite
|
Sign up to set email alerts
|

Clinical applications of infusion systems

Abstract: Continuous delivery of drugs from portable and implantable pumps offers several advantages over intermittent therapy, including control and maintenance of blood levels of the drug within a narrow therapeutic range, and increased predictability of response. Clinical applications are discussed in the areas of diabetes mellitus, infertility and delayed puberty, iron overload, anticoagulation, analgesia, prevention of premature labour, cardiac arrhythmias, dissolution of gallstones and anticancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

1985
1985
2003
2003

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 65 publications
0
1
0
1
Order By: Relevance
“…Previous experience has shown that closed-loop BSL control using real-time continuous measure-ments of venous whole blood glucose level is viable and effective in glycaemic regulation [3][4][5] . Older systems however suffered many problems with the glucose sensor, limiting the length of treatment possible [6][7][8] . The portability of the older systems was also very limited 1,7 .…”
mentioning
confidence: 99%
“…Previous experience has shown that closed-loop BSL control using real-time continuous measure-ments of venous whole blood glucose level is viable and effective in glycaemic regulation [3][4][5] . Older systems however suffered many problems with the glucose sensor, limiting the length of treatment possible [6][7][8] . The portability of the older systems was also very limited 1,7 .…”
mentioning
confidence: 99%
“…Vem crescendo o interesse por formulações e vias de administração que promovam a localização/direcionamento de fármacos ao sítio alvo e contornem seus efeitos adversos sistêmicos, o que, na maioria das vezes, está associado à baixa adesão ao tratamento (52)(53)(54)(55). Além disso, a possibilidade de redução da frequência de dosagem é geralmente associada à melhoria da adesão aos tratamentos, principalmente crônicos.…”
Section: Liberação Sustentada E Sistemas De Liberação Líquidocristalinounclassified